MARITIME SECURITY PERSPECTIVE IN THE CASE STUDY OF DEEPWATER HORIZON - Verdinand Robertua; Angel Damayanti (Sociae Polites, 2021)
Maritime security still focuses on the territorial sovereignty of a country. Environmental disasters and transboundary humanitarian crimes that occur at sea are a challenge for International Relations academics to reformulate maritime security. British Petroleum (BP) is negligent in implementing safety standards in oil exploration and exploitation in the Gulf of Mexico, United States resulting in oil leakage on the Deepwater Horizon platform. This research uses the Deepwater Horizon case study in exploring the relevance of maritime security in the prevention and management of marine pollution disasters. Primary data sources were taken from observations of researchers in seminars related to the Deepwater Horizon and secondary data were obtained from journals, electronic news and official reports from the US Government. There are two findings obtained. First, contemporary maritime security is much more complex than traditional maritime security and second, contemporary maritime security involves an element of justice seeking as demonstrated by the United States Court's decision against BP regarding negligence in the Deepwater Horizon. Keywords: Maritime Security, United States of America, Deepwater Horizon, British Petroleum